THE EFFECT OF THE PROBLEM-BASED LEARNING (PBL) MODEL AND SELF-EFFICACY ON CRITICAL THINKING SKILLS - Yunidawati Yunidawati; Nurrohmatul Amaliyah; Budhi Akbar (Jurnal Buah Hati, 2026)
Science learning in Grade V at SDN Ciganjur 04 is still teacher-centered, causing students to be passive, limiting the development of critical thinking skills, and resulting in low self-efficacy in learning. This study aims to analyze the effect of the Problem Based Learning (PBL) model and self-efficacy on students’ critical thinking skills. This research employed a quantitative experimental method with a 2×2 factorial design. The sample consisted of 64 students, including 32 students in the experimental class (PBL) and 32 students in the control class (conventional learning), selected using saturated sampling technique. Data were analyzed using a two-way ANOVA test. The results showed that: (1) there is a significant effect of the PBL model on critical thinking skills (Fcount = 11.248 > Ftable = 4.210); (2) there is a significant effect of self-efficacy on critical thinking skills (Fcount = 6.704 > Ftable = 4.210); and (3) there is a significant interaction effect between the PBL model and self-efficacy on critical thinking skills (Fcount = 11.991 > Ftable = 4.210). Therefore, the implementation of the PBL model supported by high self-efficacy can optimally improve students’ critical thinking skills.